"Because the World Consists of Everybody": Understanding Parents' Preferences for Neighborhood Diversity. (June 2020) - Darrah–Okike, Jennifer; Harvey, Hope; Fong, Kelley
Previous research, primarily using survey data, highlights preferences about neighborhood racial composition as a potential contributor to residential segregation. However, we know little about how individuals, especially parents, understand neighborhood racial composition. We examine this question using in–depth interview data from a racially diverse sample of 156 parents of young children in two metropolitan areas. Prior scholarship on neighborhood racial preferences has mostly been animated by expectations about in–group attraction, out–group avoidance, the influence of stereotypes, and perceived associations between race and status. However, we find that a substantial subset of parents expressed a desire for racially and ethnically mixed neighborhoods—a residential preference at odds with racial segregation. Parents across race conceptualized neighborhood diversity as beneficial for children's development. They expressed shared logics, reasoning that neighborhood diversity cultivates skills and comfort interacting with racial others; teaches tolerance; and provides cultural enrichment. However, these ideas intersected with racial segregation and stratification to shape parents' understandings of diversity and hinder the realization of parents' aspirations. Beliefs about the benefits of neighborhood diversity were rarely a primary motivation for residential choices. Nonetheless, parents' perceptions of the advantages of neighborhood racial mixing reveal the reach of discourse on the value of diversity and suggest a potential opportunity to advance residential desegregation.